Forest stand biomass and NPP models sensitive to winter tempera-ture and annual precipitation for Betula spp. in Eurasia - Andreevich Usoltsev, Vladimir; Zukow, Walery; Stepanovich Tsepordey, Ivan; Petrovich Chasovskikh, Viktor (Ecological Questions, 2020)
Forest ecosystems, as sinks of atmospheric carbon, play an important role in reduc-ing CO2 emissions and preventing annual temperatures from rising. On the other hand, cli-mate change entails changes in the structure and functions of all the biota, including forest cover. Therefore, we attempted to model Betula spp. ecosystem biomass and annual net pri-mary production (NPP) (t ha-1) using the data from 650 forest stands for biomass, 245 for NPP and biomass, as well as climate data on the Trans-Eurasian hydrothermal gradients. The model involves regional peculiarities of age and morphology of the forests. It is found that the reaction of birch biomass and NPP structure on temperature and precipitation corresponds to the principle of limiting factors by Liebig-Shelford but in different proportions for different species. Since the minimum values of biomass and NPP occur in regions with minimum pre-cipitation and minimum temperature, these two factors are limiting in terms of biomass and NPP of birches. The same phenomenon is typical for firs, partly typical for spruces and very differ for larches and pines. The development of such models for basic forest-forming species grown in Eurasia will give possibility to predict any changes in the biological productivity of forest cover of Eurasia in relation to climate change.